2019
DOI: 10.3390/foods8100517
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Pressure Processing on Polyphenol Oxidase Activity, Phytochemicals and Proximate Composition of Irish Potato Cultivars

Abstract: Polyphenol oxidase (PPO) activity, proximate composition, and phytochemicals were determined in four common Irish potato cultivars following a high pressure processing (HPP) at 600 MPa for 3 min. PPO activity was significantly (p < 0.05) lower in all HPP treated samples, while the overall proximate composition was not affected. The total phenolic content was significantly higher in the HPP treated samples. Chlorogenic acid levels significantly decreased with simultaneous increase of caffeic acid and p-coumaric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 41 publications
5
23
2
Order By: Relevance
“…Fresh potato tubers had a TSP value of 0.30 ± 0.01 mg GAE/g wet basis (w.b. ), which was similar to values reported in the previous studies (Teoh et al., 2016; Tsikrika, O'Brien, & Rai, 2019). Figure 7 shows the effects of different freezing methods on TSP content of potatoes thawed for 1 hr (before browning development).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Fresh potato tubers had a TSP value of 0.30 ± 0.01 mg GAE/g wet basis (w.b. ), which was similar to values reported in the previous studies (Teoh et al., 2016; Tsikrika, O'Brien, & Rai, 2019). Figure 7 shows the effects of different freezing methods on TSP content of potatoes thawed for 1 hr (before browning development).…”
Section: Resultssupporting
confidence: 92%
“…In addition, Tsikrika et al. (2019) also observed a 20% increase in TSP content in potato tubers following high‐pressure treatments of 600 MPa for 3 min. The increase in the phenolic contents during isochoric freezing could be due to an increase in phenylalanine ammonia‐lyase activity from cell injury that induced an increase in the concentration of phenolic compounds (Saltveit, 1997).…”
Section: Resultsmentioning
confidence: 91%
“…PPO inactivation of 57% was achieved when cloudy carrot juice was subjected to HPP at 600 MPa (Stinco et al 2019). Tsikrika et al (2019) investigated HPP of Irish potato cultivars at 600 MPa for 3 minutes and reported lower PPO activity and higher total phenolic content in all HPP treated samples in vacuum sealed polyethylene/ polyamide pouches. High pressure processed vegetable High Pressure Processing of Fruits and Vegetables: A Review smoothie showed a reduction in PPO activity of 16.7% at 630 MPa for 6 minutes (Fernandez et al 2020).…”
Section: Polyphenol Oxidasementioning
confidence: 99%
“…In addition, the impacts of thermal and emerging non-thermal food processing methods on the fate of phytochemicals are scarce. In this special issue, phytochemicals responsible for various biological activities have been investigated with advanced analytical techniques including liquid chromatography tandem mass spectrometry (LC–MS/MS), nuclear magnetic resonance (NMR) spectroscopy and molecular-docking experiments [ 1 , 2 , 3 , 4 , 5 ]. The impact of domestic thermal processing and non-thermal (high-pressure processing) on the phytochemicals has also been covered.…”
mentioning
confidence: 99%
“…Here, the roasting of broomcorn millet ( Panicum miliaceum L.) significantly enhanced the antioxidant polyphenols, in particular ferulic acid, as opposed to steaming, puffing and extrusion [ 6 ]. High-pressure processing at 600 MPa for 3 min of potatoes significantly reduced the polyphenol oxidase activity and the polyphenol responsible for potato browning, i.e., chlorogenic acid, without impacting antioxidant capacity as well as the cytotoxic glycoalkaloids (α-solanine and α-chaconine) contents [ 5 ]. Caffeic acid derivatives, in particular salvianic acid A, from the leaves of Actinidia arguta (Hardy Kiwi) have been linked for anti-inflammatory properties [ 2 ].…”
mentioning
confidence: 99%